Spatiotemporal vegetation dynamics in South Asia (2001-2023): roles of climate and anthropogenic activities - Ghani Rahman; Umar Farooq; Min-Kyu Jung; Hyun-Han Kwon (Geoscience Letters)
Abstract Vegetation maintains ecological balance, supports biodiversity, and influences regional climate patterns. This study evaluated vegetation changes across South Asia (2001–2023) using NDVI data from MODIS satellites. Climatic and anthropogenic factors influencing vegetation were examined through the Mann–Kendall trend test, Sen’s slope estimator, residual trend analysis, and Hurst exponent analysis. Results indicated a widespread greening trend driven by afforestation, improved irrigation, and sustainable land management. Vegetation decline (16.9% from residual trend analysis) was observed in urbanized and deforested areas. Precipitation emerged as the primary climatic driver, with approximately 70.5% of vegetated regions showing positive correlations with rainfall. Temperature effects were spatially varied, extending growing seasons in high-altitude regions such as the Hindu Kush and Himalayas, while contributing to vegetation stress in arid zones. Residual trend analysis highlighted human influence, with 83.1% of vegetated areas showing positive trends. Hurst exponent analysis predicted persistent greening (96.5%), emphasizing the importance of climate-resilient land management policies, targeted afforestation, and sustainable agricultural practices to promote ecological resilience. Keypoints Vegetation in South Asia increased from 2001 to 2023 due to afforestation, irrigation, and sustainable land management efforts. Precipitation mainly drives vegetation growth, while temperature impacts vary, benefiting highlands but stressing arid regions. Human activities boosted vegetation in 83.1% of areas, but 16.9% faced losses due to urbanization, deforestation, and land degradation. Plain Language Summary This study explores changes in vegetation across South Asia from 2001 to 2023, using satellite data to understand the impacts of climate and human activities. The results revealed that vegetation is increasing in many areas due to afforestation, improved irrigation, and sustainable land management practices. However, vegetation loss is prominent in urbanizing and deforested regions. Rainfall was found to be the most important climatic factor for vegetation health, with most regions showing a strong positive link between rainfall and vegetation growth. Temperature effects varied; increasing temperature extended growing seasons in high-altitude regions but stressed plants in arid areas. The study also highlights human efforts, such as afforestation and land management, which have improved vegetation in many areas. Despite this progress, some regions face long-term vegetation decline, emphasizing the need for targeted conservation policies to ensure ecological resilience across South Asia.